Multipurpose composite lithium-based lubricating grease and preparation method thereof

Through oxidation and modification of cypress oil, combined with the complexity of 12-hydroxyl fatty acid and lipidic acid and the addition of mitigation oxidation, solve the decreased adhesion and resistance of composite lithium-based lubricating fat at high temperature at high temperatures. The problem of insufficient corrosiveness realizes the efficient stability and multifunctional properties of grease.

CN119331674AActive Publication Date: 2025-01-21NATOR LUBRICATION TECH JIANGSU CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411434317.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-21
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing composite lithium-based grease has reduced adhesion and is easy to disengage the equipment at high temperatures, and has insufficient corrosion resistance and stability, making it difficult to meet the demanding requirements of modern industry for lubricants.

Method used

By oxidizing and modified epoxy resin, the modified rice oil oil is used to increase the force of the hydrogen bonding of the lubricating fat; the use of 12-hydroxyl fatty acid and stearic acid to form a stable skeleton structure; add Modified graphene and alpha-layer-like phosphate and calcium carbonate are reproduced to improve conductive performance and abrasion performance.

Benefits of technology

It improves the work cone in composite lithium -based lubricating fat, extended cones, high temperature resistance, acid corrosion resistance and abrasion performance, enhance the stability and conductive performance of grease, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331674A_ABST
    Figure CN119331674A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lubricating grease preparation, in particular to multipurpose composite lithium-based lubricating grease and a preparation method thereof. The composite lithium-based lubricating grease comprises base oil, a composite lithium-based thickening agent and an additive, and is prepared by wrapping the base oil in a framework structure of the composite lithium-based thickening agent through a high-temperature micro-pressure reaction kettle. The epoxy resin is used for modifying the epoxidized castor oil, so that the prepared lubricating grease is small in penetration change and good in stability and has acid corrosion resistance; the fatty acid is compounded with different types of auxiliary acids, so that the prepared composite lithium-based lubricating grease is high in dropping point and resistant to high temperature; the lubricating grease prepared by modifying the graphene oxide through the ionic liquid is low in volume resistivity and high in conductivity, and can be used for lubricating electronic components; the alpha-layered zirconium phosphate and the calcium carbonate are compounded for use, so that the prepared lubricating grease is good in wear resistance and suitable for long-time lubrication work.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grease preparation, in particular to a multi-purpose composite lithium-based grease and a preparation method thereof. Background Art

[0002] Friction and wear are the main causes of energy consumption and equipment damage in mechanical equipment. In the process of promoting the concept of sustainable development globally, the importance of saving energy and materials has become increasingly prominent. Lubrication technology is the main means to reduce friction and wear. With the development of modern industry, the harsh operating conditions of mechanical equipment and the diversification of working conditions have continuously put forward more stringent requirements for lubricants, and it is urgent to develop lubricants that are compatible with the development.

[0003] Grease is an important component of industrial lubricants. Grease technology has been developing continuously since its birth, and has formed a series of rich lubricating products. As mechanical equipment develops towards large-scale, miniature, high-speed, heavy-load, vacuum, low-temperature, ultra-high precision, automation and intelligence, people's demand for new high-performance lubricating products is also increasing. The development of high-performance grease products with long life and reliable lubrication for use in multiple occasions has huge market prospects and economic benefits.

[0004] Composite lithium-based grease is a high-temperature multi-effect grease developed in the 1960s. Compared with lithium-based grease, it is more suitable for use at high temperatures, has good multi-effect performance, and has strong thickening ability for various types of mineral oils and synthetic oils. However, with the development of modern industry, industrial sectors such as food, automobiles, printing and dyeing, mining, metallurgy, and aerospace have put forward increasingly stringent requirements on the oxidation resistance, high and low temperature resistance, extreme pressure and anti-wear performance, water resistance, and mechanical stability of grease.

[0005] Patent CN109810748B reports lithium-based grease and its preparation method, including base oil, anti-wear agent, rust inhibitor, antioxidant, lubricant, thickener, saponifier, the thickener is dodecyl hydroxystearic acid, the saponifier is selected from lithium hydroxide monohydrate, and the lithium-based grease has excellent stability and wear resistance. However, the dropping point of this type of grease is not high, the adhesion decreases at high temperature, and oil separation occurs. When an organic rust inhibitor and antioxidant are used, the grease will not only cause poor lubrication and damage to the equipment after it is separated from the equipment, but may also cause environmental pollution.

[0006] Patent CN112877121B reports a grease and its preparation method and application, which uses mineral oil as base oil, composite lithium base as thickener, and adds antioxidants, rust inhibitors, and extreme pressure anti-wear agents to prepare the grease. The grease has good low-temperature resistance, but the cone penetration is large and the grease stability is poor, which limits the further use of the grease.

[0007] Patent CN109536260B reports an environmentally friendly grease with high lubrication performance and a preparation method thereof, which comprises base oil, 12-hydroxystearic acid, lithium hydroxide powder, composite heat stabilizer, auxiliary heat stabilizer, carboxymethyl cellulose, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, antioxidant, graphite and glycerol; the grease prepared by the invention uses environmentally friendly additives, which increases the biodegradability of the grease and has little pollution to the environment; however, the addition of a large amount of additives leads to uneven particle size distribution, and there is a trend of decreasing the total surface area of ​​the particle phase, thereby accelerating the surface hardening phenomenon of such grease, while reducing the wear resistance of the grease and reducing the lubrication effect.

[0008] Patent CN102051257B reports a composite lithium-based grease and its production process. The composite lithium-based grease is prepared by uniformly mixing 12-hydroxystearic acid, sebacic acid, lithium hydroxide, composite calcium sulfonate grease, base oil, tackifier, multifunctional agent, antioxidant, and metal passivator. The grease has good lubrication performance in water-rich and heavy-load situations and extends the life of the bearing. The addition of additives changes the performance of the grease, but also reduces the corrosion resistance of the grease. The lubrication performance is reduced under long-term use conditions, which limits the use of the lubricant.

[0009] Grease forms a lubricating film between the inner ring, outer ring and rolling elements of the bearing. When the shaft voltage on both sides of the oil film exceeds the threshold, the lubricating film will be broken down, generating a large instantaneous current, which will cause damage to the rolling elements and raceway surfaces. This phenomenon is called "electrical corrosion". Industrial development has made the operating conditions of motor bearings and electronic components more complex, and the failure modes of work are diverse, including electrical corrosion, pitting, plastic deformation, wear and fatigue. However, bearings are one of the key components of mechanical equipment and play a vital role in precision machinery. Therefore, the lubrication of bearings and electronic components also requires grease to have certain conductive properties.

[0010] Patent CN102618359B reports a silicon-based grease composition for electrical contacts and a preparation method thereof, comprising a silicon-based base oil, a thickener, and an additive, wherein the thickener is a complex lithium soap, and graphite or zinc oxide is added as a conductive material to improve the conductive properties of the grease; however, the addition of solid conductive materials can improve the high temperature resistance and conductive properties of the grease, but the fluidity and lubricity are poor, and at the same time, the large amount of inorganic matter added further improves the antioxidant and corrosion resistance of the grease.

[0011] In summary, composite lithium-based grease is used in the prior art to improve the performance of grease, and can be used in different lubrication occasions, but there are still some shortcomings; the grease has poor high temperature resistance, low adhesion, and the grease is easy to detach from the equipment, and the high temperature lubrication performance is poor; the residual alkali in the preparation process of the grease has poor oxidation stability, which affects the corrosion resistance of the grease, and the stability is low, which is not conducive to the long-term effect of the grease; at the same time, it has the disadvantages of hardening tendency, poor rust resistance, large change in high temperature cone penetration, poor wear resistance, and poor lubrication effect; at the same time, it is used in different mechanical fields, such as motor bearings and electronic components, and it still needs to have certain conductivity while having good lubrication properties. The base oil or thickener used in the prior art is not environmentally friendly, and has certain application restrictions in industries with environmental protection requirements.

[0012] Therefore, a multi-purpose composite lithium-based grease and a preparation method thereof are proposed. Summary of the invention

[0013] The object of the present invention is to provide a multi-purpose composite lithium-based grease and a preparation method thereof. The modified castor oil is obtained by oxidizing castor oil and modifying it with epoxy resin, and the hydrogen bonding force in the grease is increased. The working cone penetration of the composite lithium-based grease is 242 / 0.1mm, the extended working cone penetration is 275 / 0.1mm, and the stability is improved. By compounding 12-hydroxystearic acid with stearic acid and changing the dosage of auxiliary acid and fatty acid, the dropping point of the composite lithium-based grease is 326°C, the oil separation rate of the steel mesh is 1.28%, and the temperature resistance is improved. By modifying the epoxidized castor oil and controlling the dosage of the modifier, the copper sheet acid corrosion and steel sheet acid corrosion of the composite lithium-based grease are 1a and 1a respectively, and the acid corrosion resistance is improved. The oxidized graphene is modified by using ionic liquid to increase the compatibility of solid graphene in the grease, and the volume resistivity of the composite lithium-based grease is 0.82×10 9 Ω·cm, can be used for the lubrication of electronic components; by using α-layered zirconium phosphate and calcium carbonate in combination, the steel ball wear spot diameter of the prepared composite lithium-based grease is 0.35mm, the average friction coefficient is 0.091, and the anti-wear performance is good.

[0014] To achieve the above object, the present invention provides the following technical solutions:

[0015] On one hand, the present invention provides a method for preparing a multi-purpose composite lithium-based grease, characterized in that: the composite lithium-based grease comprises 75-100 parts of base oil, a composite lithium-based thickener, and additives;

[0016] The composite lithium-based thickener includes 5-10 parts of 12-hydroxystearic acid, 1.5-4 parts of stearic acid, auxiliary acid, and 0.8-2 parts of lithium hydroxide;

[0017] The additives include 5-15 parts of modified graphene oxide, 4-13 parts of anti-wear agent, antioxidant, and rust inhibitor;

[0018] The modified graphene is prepared by modifying graphene oxide and ionic liquid in a ratio of 1-4:6-9;

[0019] The preparation method of the multi-purpose composite lithium-based grease comprises the following steps:

[0020] The lithium hydroxide is added into deionized water and stirred to obtain a lithium hydroxide solution; 50% of the base oil, the 12-hydroxystearic acid and the stearic acid are added into a flask to obtain a dissolving system; the lithium hydroxide solution is added into the dissolving system, the temperature is raised to 95-100° C., and the system is saponified for 2 hours to obtain a system 1; the auxiliary acid is added into the system 1, the remaining amount of the lithium hydroxide solution is raised to 120-130° C., and the system is saponified for 1 hour to obtain a system 2; the system 2 is raised to 180-190° C., and the system is stirred and kneaded for 3 hours. 0min to obtain system three; add 25% of the base oil in total to the system three, slowly heat up to 220-225°C, and refine for 20min to obtain system four; add the remaining base oil to the system four, cool to 120°C, and keep warm for 10min to obtain composite grease; add the modified graphene oxide, the anti-wear agent, the antioxidant, and the rust inhibitor to the composite grease, stir at 90°C for 30min to obtain a mixture; transfer the mixture to a degassing kettle for degassing, filter, and package to obtain the composite lithium-based grease.

[0021] Preferably, the base oil is selected from modified castor oil, white oil, cycloalkyl oil, and poly-alpha-olefin oil.

[0022] Preferably, the preparation method of the modified castor oil comprises the following steps:

[0023] Castor oil, glacial acetic acid and phosphoric acid are added into a three-necked flask to obtain a mixture; the mixture is stirred, the temperature is raised to 70° C., 30% H2O2 solution is slowly added dropwise into the mixture, and the mixture is kept warm for 4 hours to obtain a reaction solution; the reaction solution is extracted with petroleum ether, rotary evaporated, and vacuum dried to obtain epoxidized castor oil; the epoxidation degree of the epoxidized castor oil is 0.5-2.2 mol / kg;

[0024] The modifier is added into a three-necked flask, and 50 ml of ethanol is added and stirred to dissolve to obtain a solution; 100 parts of the epoxidized castor oil is slowly added into the solution, and the reaction is carried out at 50° C. for 2 hours to obtain a reaction liquid; the reaction liquid is cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried at 80° C. for 2 hours to obtain the modified castor oil.

[0025] Preferably, the modifier is selected from one of polymethacrylate, polyethylene, epoxy resin E42, epoxy resin E44, and bisphenol F; the amount of the modifier is 1-5 parts.

[0026] Preferably, the auxiliary acid is selected from azelaic acid, adipic acid, boric acid, terephthalic acid, and dodecanedioic acid.

[0027] Preferably, the ionic liquid is selected from one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-decyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium di(trifluoromethylsulfonyl)imide, 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and bis(trifluoromethylsulfonyl)imide.

[0028] Preferably, the preparation method of modified graphene oxide comprises the following steps:

[0029] Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:1 to obtain a mixed acid solution; graphite and a 30% hydrogen peroxide solution are added to the mixed acid solution, and an ultrasonic reaction is performed for 2 hours to obtain a graphene solution; the graphene solution is centrifuged to obtain a solid separation; the solid separation is washed with a hydrochloric acid solution with a volume fraction of 10%, washed with deionized water, and vacuum dried at 80°C to obtain graphene oxide; the graphene oxide is added to anhydrous acetone, the ionic liquid is added under stirring, and ultrasonic dispersion is performed to obtain a mixed solution; the mixed solution is ground at room temperature for 4 hours to obtain a grind; the grind is placed in a vacuum drying oven and dried at 80°C for 24 hours to obtain the modified graphene oxide.

[0030] Preferably, the anti-wear agent is selected from a mixture of α-layered zirconium phosphate and calcium carbonate; the α-layered zirconium phosphate is used in an amount of 1-10 parts, with a particle size of 600-800 nm; and the calcium carbonate is used in an amount of 1-5 parts.

[0031] Preferably, the antioxidant is selected from tert-butyl-4-hydroxyanisole, and the rust inhibitor is selected from zinc naphthenate.

[0032] On the other hand, the present invention provides a multi-purpose composite lithium-based grease, characterized in that: the composite lithium-based grease comprises the base oil, the composite lithium-based thickener, the modified graphene oxide, the anti-wear agent, the antioxidant, and the rust inhibitor; the composite lithium-based grease is prepared by the preparation method according to any one of claims 1 to 9; the working cone penetration of the composite lithium-based grease is 242 / 0.1mm, and the extended working cone penetration is 275 / 0.1mm; the dropping point of the composite lithium-based grease is 326°C, and the steel mesh oil separation rate is 1.28%; the copper sheet acid corrosion and steel sheet acid corrosion of the composite lithium-based grease are 1a and 1a respectively; the volume resistivity of the composite lithium-based grease is 0.82×109 Ω·cm; the diameter of the steel ball wear spot of the composite lithium-based grease is 0.35mm, and the average friction coefficient is 0.091.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention obtains epoxidized castor oil by oxidizing castor oil under acidic conditions, controls the epoxidation degree to improve the viscosity of the epoxidized castor oil, and modifies the castor oil to obtain an innovative means of modified castor oil; the presence of epoxy bonds is utilized to enhance the hydrogen bonding effect in the grease, increase the cohesive force of the grease molecules, and fully wrap the base oil in a three-dimensional skeleton structure, thereby reducing the difference in the working cone penetration of the grease; the stability of the composite lithium-based grease is enhanced and improved, and the base oil used is a food-grade base oil, which has broad application prospects in industries that have color requirements or environmental protection requirements for the appearance of the grease, and is suitable for use in the food processing industry.

[0035] 2. The present invention uses 12-hydroxystearic acid and stearic acid in combination, utilizes the electrostatic attraction between the carboxyl oxygen atoms in the stearic acid crystals and the auxiliary acid lithium crystals and the lithium ions, and forms a co-crystal through strong interaction to produce an innovative means of producing a composite lithium-based thickener with a stable skeleton structure. The food-grade grease thickener achieves high temperature resistance of the composite lithium-based grease, and enhances and improves the oil separation rate of the steel mesh, and is suitable for use in food processing and high-temperature lubrication conditions.

[0036] 3. The present invention enhances the viscosity of the modified castor oil by using epoxy resin to modify epoxidized castor oil. At the same time, the polar group introduced can be more compatible with the composite lithium-based thickener. At the same time, the epoxy resin can form a covalent bond with -OH, thereby enhancing the intermolecular force. The innovative means of forming a three-dimensional network cross-linked structure achieves the improvement of the corrosion resistance of the composite lithium-based grease, especially the acid corrosion resistance, and is suitable for use under acidic conditions.

[0037] 4. The present invention increases the conductivity of grease by adding graphene oxide, and increases the compatibility of graphene oxide with grease base oil by modifying graphene oxide with ionic liquid. The innovative method of modifying graphene oxide with ionic liquid is used to improve and enhance the conductivity of composite lithium-based grease. The improved conductivity is suitable for the lubrication of electronic components and electronic products.

[0038] 5. The present invention uses α-layered zirconium phosphate and calcium carbonate in combination, and adds them to the composite lithium-based grease. Through the innovative method of compounding layered zirconium phosphate and calcium carbonate, the average friction coefficient of the composite lithium-based grease and the diameter of the wear spot of the steel ball are improved, the anti-wear performance of the grease is improved, the long-term operation of the grease under high pressure and acidic working conditions is facilitated, and the use cost of the grease is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a SEM image of the α-layered zirconium phosphate prepared in Example 56;

[0040] Figure 2 This is a graph showing the change in the volume wear of the steel disk and the wear spot diameter of the steel ball with the amount of α-layered zirconium phosphate used in the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0043] The white oil of the present invention is selected from food grade white oil produced by Mobil Corporation of the United States.

[0044] The naphthenic oil of the present invention is selected from naphthenic oil 100SN, which is produced by Mobil Corporation of the United States.

[0045] The polyalphaolefin oil of the present invention is selected from PAO40, which is purchased from ExxonMobil Corporation.

[0046] See also Figure 1 to Figure 2 The present invention provides a multi-purpose composite lithium-based grease and a preparation method thereof, and the technical scheme is as follows:

[0047] Examples 1-5

[0048] Preparation of epoxidized castor oil:

[0049] 60 parts of castor oil, 9 parts of glacial acetic acid and 0.6 parts of phosphoric acid are added into a three-necked flask, and a thermometer, a reflux condenser and a dropping funnel are provided to obtain a mixture. The mixture is stirred until the oil bath temperature reaches 70° C. 6-48 parts of a 30% H2O2 solution are slowly added dropwise to the mixture, and the mixture is kept warm for reaction for 4 hours to obtain a reaction solution. The reaction solution is extracted with petroleum ether, rotary evaporated, and vacuum dried to obtain epoxidized castor oil. The epoxidation degree of the epoxidized castor oil is quantified according to ISO 3001:1999 standard, and the epoxidation degree is shown in Table 1.

[0050] Table 1 Epoxy Degree Results of Examples 1-5

[0051] Example Base oil Glacial acetic acid / part Phosphoric acid / part <![CDATA[30% H2O2 solution / part]]> Epoxy degree (mol / kg) Example 1 castor oil 9 0.6 6 0.5 Example 2 castor oil 9 0.6 12 1.2 Example 3 castor oil 9 0.6 24 1.6 Example 4 castor oil 9 0.6 36 1.9 Example 5 castor oil 9 0.6 48 2.2

[0052] Example 6

[0053] Add 3 parts of epoxy resin into a three-necked flask, add 50 ml of ethanol and stir to dissolve, to obtain a resin solution; weigh 100 parts of the epoxidized castor oil prepared in Example 1, slowly add it into the resin solution, and react at 50° C. and 400 r / min for 2 h to obtain a reaction solution; cool the reaction solution to room temperature, remove the solvent by rotary evaporation, and vacuum dry at 80° C. for 2 h to obtain the modified castor oil.

[0054] Add 1.5 parts of lithium hydroxide to 15 ml of deionized water and stir evenly to obtain a lithium hydroxide solution; add half of the total amount of the modified castor oil, 8 parts of 12-hydroxystearic acid, and 1.5 parts of stearic acid to a three-necked flask, heat to 80°C, and keep warm for 30 minutes to obtain a dissolving system; add 1 part of the lithium hydroxide solution to the dissolving system, heat to 100°C, and saponify at a constant temperature for 2 hours to obtain a saponification system 1; add 2.5 parts of azelaic acid to the saponification system 1, and 0.5 parts of the lithium hydroxide solution are heated to 120°C, and saponified at a constant temperature for 1 hour to obtain a saponification system 2; heat the saponification system 2 to 180°C, knead at a constant temperature for 30 minutes, and accelerate stirring. The invention relates to a method for preparing a saponification system 3 by mixing the modified castor oil in an amount of 25% by total weight into the saponification system 3, slowly heating the temperature to 210° C., and refining the mixture at the temperature for 20 min to obtain a saponification system 4; the remaining modified castor oil is added into the saponification system 4, the temperature is lowered to 120° C., and the mixture is refining the mixture at the temperature for 10 min to obtain a composite grease; 10 parts of modified graphene oxide, 5 parts of α-layered zirconium phosphate, 3 parts of calcium carbonate, 0.5 parts of tert-butyl-4-hydroxyanisole, and 0.5 parts of zinc cyclohexane are added into the composite grease, and the mixture is stirred at 90° C. for 30 min to obtain a mixture uniformly; the mixture is transferred to a degassing kettle for degassing, filtered, and then packaged to obtain the composite lithium-based grease.

[0055] Examples 7-10 refer to the preparation method and parameter conditions described in Example 6, except that the modified castor oil prepared in Examples 2-5 is used respectively.

[0056] Examples 11-19 refer to the preparation methods and parameter conditions described in Example 6, with the differences shown in Table 2.

[0057] Comparative Example 1 refers to the preparation method and parameter conditions described in Example 6, except that castor oil is used as the base oil.

[0058] Comparative Example 2 refers to the preparation method and parameter conditions described in Example 6, except that epoxidized castor oil is used as the base oil.

[0059] Example 20 Stability Performance Determination

[0060] The working cone penetration and extended cone penetration of the greases prepared in Examples 6-19 and Comparative Examples 1-2 were tested to evaluate the stability of the prepared greases. The test results are shown in Table 2.

[0061] Working cone penetration: Put the grease sample into a standard working device. At 25°C, after 60 shears, the measured cone penetration is 0.1mm. It is measured in accordance with GT / T269-1991 standard.

[0062] Extended working cone penetration: The cone penetration of the grease is measured after 100,000 shears in a standard working machine at 25°C, 0.1mm; measured in accordance with GT / T269-1991 standard.

[0063] The cone penetration tester model is BF-38A.

[0064] Table 2 Stability performance determination of Examples 6-19

[0065]

[0066] The results in Table 2 show that the unmodified castor oil used in Comparative Example 1 shows a significantly reduced viscosity, the prepared grease has a high working cone penetration, the grease is in a liquid state, and the bonding performance is poor, and it cannot be used for the lubrication of daily mechanical bearings; in Comparative Example 2, the epoxidized castor oil modified with epoxy resin is not added, and the working cone penetration of the prepared grease is significantly reduced compared with that of Comparative Example 1, and the grease has good stability. Since the epoxy resin contains a large number of epoxy bonds, the force of its hydrogen bonds can be enhanced. In addition, the epoxy resin forms a covalent bond with the -OH in the epoxidized castor oil, thereby also enhancing the intermolecular force and improving Working cone penetration and extended cone penetration of grease; The results of Examples 6-15 show that when different base oils are used as the base oil of grease, the stability of the grease is significantly different due to the difference in the properties of the prepared lubricating oils. The cone penetration of the grease synthesized from paraffin base oil is significantly smaller than that of the grease synthesized from poly-alpha olefin oil. Since poly-alpha olefin oil has a highly polymerized molecular chain with weak polarity, it is difficult for the polar groups in the composite lithium group to bond to form a skeleton structure, which reduces its thickening ability and improves the working cone penetration; the same cycloalkyl oil has a reduced thickening ability due to the interaction of the rigid cycloalkyl groups; with the increase of the cycloalkyl group, the cycloalkyl group of ... The increase of oxygen value shows a significantly improved cone penetration, which improves the application of grease in mechanical lubrication. Due to the increase of oxidation value, the cross-linking of modified castor oil in the composite lithium-based thickener is increased. The presence of epoxy bonds enhances the hydrogen bonding effect in the grease, increases the cohesion of the grease molecules, and fully wraps the base oil in the three-dimensional skeleton structure, thereby improving the working cone penetration of the grease and enhancing the stability of the grease. It can be seen from the results of Examples 16-19 and Example 10 that with the increase of the number of base oils, the working cone penetration gradually increases; the base oil content is relatively low, and the rigid network structure reduces the viscosity of the grease. The grease is hard, has poor lubrication effect and low stability; increasing the amount of base oil can increase the viscosity of the grease and increase the degree of crosslinking with the thickener, but too high viscosity leads to high fluidity of the grease, which cannot be fully adsorbed by the skeleton structure, resulting in poor lubrication effect. At the same time, the exposed epoxy groups are easily affected by the environment, reducing the stability of the grease; From the results in Table 2, it can be seen that by using epoxy resin to modify castor oil and controlling the amount of base oil, the working cone penetration of the prepared composite lithium-based grease is 242 / 0.1mm, the extended working cone penetration is 275 / 0.1mm, the shear resistance is enhanced, and the stability is significantly improved.

[0067] Examples 21-36

[0068] Add 0.8-2 parts of lithium hydroxide to 15 ml of deionized water and stir evenly to obtain a lithium hydroxide solution; take 45 parts of the modified castor oil obtained in Example 5, weigh 5-10 parts of 12-hydroxystearic acid and 1.5-4 parts of stearic acid, add them to a three-necked flask, heat to 80°C, and keep warm for 30 minutes to obtain a dissolution system; add half of the total amount of the lithium hydroxide solution to the dissolution system, heat to 100°C, and saponify at a constant temperature for 2 hours to obtain a saponification system 1; add 1.5-5 parts of auxiliary acid to the saponification system 1, heat the remaining amount of the lithium hydroxide solution to 120°C, and saponify at a constant temperature for 1 hour to obtain a saponification system 2; heat the saponification system 2 to 180°C, and keep constant temperature. Warm banburying for 30 minutes, accelerating stirring to obtain saponification system three; adding 20 parts of the modified castor oil to the saponification system three, slowly heating to 210°C, and keeping warm for 20 minutes to obtain saponification system four; adding 20 parts of the modified castor oil to the saponification system four, cooling to 120°C, and keeping warm for 10 minutes to obtain composite grease; adding 10 parts of modified graphene oxide, 5 parts of α-layered zirconium phosphate, 3 parts of calcium carbonate, 0.5 parts of tert-butyl-4-hydroxyanisole, and 0.5 parts of zinc cyclohexane to the composite grease, stirring at 90°C for 30 minutes, and stirring evenly to obtain a mixture; transferring the mixture to a degassing kettle for degassing, filtering, and packaging to obtain the composite lithium-based grease.

[0069] The specific differences are shown in Table 3.

[0070] Table 3 Differences in the amount of components used in Examples 21-36

[0071]

[0072] Comparative Example 3 refers to the preparation method and parameter conditions of Example 21, except that only 12-hydroxystearic acid is added.

[0073] Comparative Example 4 refers to the preparation method and parameter conditions of Example 21, except that only stearic acid is added.

[0074] Example 37 Grease Temperature Resistance Test

[0075] The dropping points of the greases prepared in Examples 19-31 were measured using a grease wide temperature range dropping point tester (SYD-3498-I), and the test standard was GT / T3498-2008.

[0076] The oil separation rate of the grease steel mesh obtained in Examples 19-31 was measured using a grease cone mesh oil separation tester (BF-54B), and the test standard was SH / TT0324-2004; the test results are shown in Table 4.

[0077] Table 4 Temperature resistance test of Examples 21-36

[0078]

[0079]

[0080] The results in Table 4 show that the dropping point of the composite lithium-based grease generated by saponification reaction of 12-hydroxystearic acid as a long-chain acid with lithium hydroxide in Comparative Example 3 is significantly higher than that of the grease formed by saponification of stearic acid and lithium hydroxide in Comparative Example 4, but the oil separation rate of the steel mesh is also significantly improved; since the hydroxyl group can strengthen the organic chain force, thereby forming a more stable soap fiber structure, the composite lithium-based grease generates electrostatic attraction between the carboxyl oxygen atoms in the 12-hydroxystearic acid crystals and the lithium azelaic acid crystals and lithium ions, and a strong interaction occurs to form a co-crystal, resulting in a stable skeleton structure, making the lubricant The grease obtains high-temperature heat resistance, and the excess hydroxyl groups are cross-linked with the base oil and are easily destroyed under high temperature, so that the oil separation rate of the steel mesh increases; the results of Examples 21-26 show that with the increase of the portion of 12-hydroxystearic acid, the dropping point of the grease gradually increases, the oil separation rate of the steel mesh gradually increases, and the colloidal stability of the grease gradually decreases; with the increase of the stearic acid content, the dropping point of the grease does not increase significantly, but the oil separation rate of the steel mesh gradually decreases. The introduction of stearic acid reduces the interaction between the base oil and the saponified lithium, while reducing the content of the hydroxyl groups, avoiding the loss of the base oil under high temperature conditions, Increase colloid stability; The results of Examples 22 and 27-33 show that with the change of the type of auxiliary acid, the dropping point of the composite lithium-based grease and the oil separation rate of the steel mesh change significantly. The preparation mechanism of the composite lithium-based grease is that long-chain fatty acids and small molecule acids associate through hydrogen bonds, and long-chain fatty acids associate through lithium bond saponification to form a composite lithium-based grease, and cross-link with the base oil to change the thickening degree of the base oil. Therefore, the composite lithium-based grease has a higher dropping point with a longer hydrogen bond length, and vice versa. The dropping point is significantly reduced because the hydrogen bond length of adipic acid composite lithium soap is longer than that of other organic dibasic acid composite lithium soaps; According to the unit cell structure By calculating the bulk modulus from the structural changes, it can be found that the bulk modulus of the composite lithium soap of azelaic acid is large due to the small molecular shape change rate under heat or external action, so the soap fiber structure is formed to absorb the base oil, which is not easy to lose, and the grease has a high dropping point; while the bulk modulus of the composite lithium soap of dodecanedioic acid and terephthalic acid is small, and the base oil in the unit cell is easily squeezed out, so the dropping point is low and the steel mesh oil separation rate is high; through the results of Example 22 and Examples 34-36, it can be seen that with the increase of the amount of lithium hydroxide, the dropping point gradually increases, the associative saponification increases, and the internal force of the grease is strong, but excessive lithium hydroxide will affect the thickening degree of the grease. From the results of Table 4, it can be seen that the composite lithium-based grease prepared by using 12-hydroxystearic acid and stearic acid in combination, selecting azelaic acid as the auxiliary acid, and controlling the acid dosage has a dropping point of 326°C and a steel mesh oil separation rate of 1.28%, which has significantly improved high temperature resistance.

[0081] Embodiment 38

[0082] Add the modifier methyl acrylate into a three-necked flask, add 50 ml of ethanol and stir to dissolve, to obtain a resin solution; weigh 100 parts of the epoxidized castor oil prepared in Example 5, slowly add it into the resin solution, and react at 50° C. and 400 r / min for 2 h to obtain a reaction solution; cool the reaction solution to room temperature, remove the solvent by rotary evaporation, and vacuum dry at 80° C. for 2 h to obtain the modified castor oil.

[0083] The preparation method and parameter conditions of the composite lithium-based grease are prepared by referring to Example 20.

[0084] Examples 39-45 refer to the preparation method and parameter conditions of Example 33, and the differences are shown in Table 5.

[0085] Comparative Example 5 refers to the preparation method and parameter conditions of Example 33, except that no modifier is added to modify the castor oil.

[0086] Example 46 Acid resistance test

[0087] The corrosion resistance of the grease was tested using a copper sheet / steel sheet with a size of 20×50×3mm. The copper sheet / steel sheet was polished before the experiment, and ultrasonically cleaned several times and dried. The grease prepared in Examples 33-40 and Comparative Example 5 was evenly applied to the dry copper sheet with a spoon to a thickness of 2mm. The copper sheet was placed obliquely in a beaker, and a 3% mass fraction HCl solution was added to the beaker, and placed at 100°C for 48h. After the experiment, the grease on the metal surface was thoroughly cleaned and dried, and compared with the standard copper sheet corrosion colorimetric card according to GB / T7326-1987. The experimental results are shown in Table 5.

[0088] Among them, 1a is a copper / steel sheet with a light yellow color, 1b is a light orange color, 2a is an orange-red color, and 2b is a purple-red color.

[0089] Table 5 Acid resistance test of Examples 38-45 and Comparative Example 5

[0090]

[0091]

[0092] The results in Table 5 show that the acid corrosion resistance of the composite lithium-based grease obtained by not using a modifier to modify the epoxy resin in Comparative Example 5 is significantly lower than that of Examples 38-45. Since the epoxidized castor oil base oil has polar epoxy groups, the hydroxyl groups are freed on the surface of the grease during the saponification process, which increases the hydrophilicity of the grease. Under acidic conditions, water molecules combine with polar groups and release active H +, enter the interior of the grease, affect the thickening performance of the lithium soap, and cause the acid resistance of the grease to decrease; the results of Examples 38-42 show that the type of modifier has a greater impact on the acid resistance. When polymethyl methacrylate contains more C=O bonds and a smaller amount is used, the colloidal structure of the lithium grease can be enhanced, but the polarity of the C=O bond is relatively strong. After reaching a certain amount, the strong polarity will affect the colloidal structure of the grease and reduce its dropping point; in addition, the interaction between polymethyl methacrylate and lithium grease is a relatively weak interatomic interaction, and no covalent bond is formed, which cannot achieve a strong interaction force to fix the colloidal structure of the lithium grease; the 12-hydroxystearate lithium soap contains The colloid structure formed by the base oil contains more -OH groups, and the hydrogen bonding force between molecules is strong. The epoxy resin contains a large number of -O- bonds, which can enhance the hydrogen bonding force; in addition, the epoxy resin can form a covalent bond with -OH, thereby also enhancing the intermolecular force, and the three-dimensional network cross-linked structure formed can effectively improve the corrosion resistance of the grease, but the excessive -OH structure will cause the increase of the oil separation rate of the grease steel mesh, and the epoxy degree of the epoxy resin should be controlled; the results of the comparative examples 38 and 43-45 show that with the increase of the epoxy resin content, the acid corrosion resistance of the grease is gradually enhanced, and all show a 1a level. It can be seen from the structure of Table 5 that the epoxy resin E42 is used as a modifier to modify the epoxidized castor oil, and the copper sheet acid corrosion and steel sheet acid corrosion of the prepared composite lithium-based grease are 1a and 1a respectively, showing a significantly improved acid corrosion resistance.

[0093] Embodiment 47

[0094] Preparation of modified graphene oxide:

[0095] Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:1 to obtain a mixed acid solution; 15 parts of graphite powder and 5 parts of 30% hydrogen peroxide solution are added to 10 ml of the mixed acid solution, and ultrasonic reaction is performed for 2 hours to obtain a graphene solution; the graphene solution is centrifuged to obtain a solid separation; the solid separation is washed with a hydrochloric acid solution with a volume fraction of 10%, washed with deionized water, and vacuum dried at 80°C to obtain graphene oxide; 9 parts of the graphene oxide are added to anhydrous acetone, 1 part of ionic liquid is added under stirring conditions, and ultrasonic dispersion is performed to obtain a mixed solution; the mixed solution is ground at room temperature for 4 hours to obtain a ground material; the ground material is placed in a vacuum drying oven at 80°C and dried for 24 hours to obtain the modified graphene oxide.

[0096] The preparation method and parameter conditions of the complex lithium-based grease are prepared by referring to Example 40.

[0097] Examples 47-57 refer to the preparation methods and parameter conditions of Example 42, and the differences are shown in Table 6.

[0098] Comparative Example 6 refers to the preparation method and parameter conditions of Example 42, except that no ionic liquid modification treatment is added.

[0099] Example 58 Conductive Performance Measurement

[0100] The volume resistivity of the composite lithium-based grease prepared in Examples 47-57 and Comparative Example 6 was measured using a GEST-121 volume resistivity tester produced by Beijing Guanshi Precision Instrument Equipment Co., Ltd. The test current was 100A and the indoor test time was 10s.

[0101] ρ=R×A / h

[0102] Where: ρ (Ω·cm) is the volume resistivity of the grease; R (Ω) is the volume resistance; A (cm 2 ) is the contact area; h (cm) is the average thickness of the sample. The measurement results are shown in Table 6.

[0103] Table 6 Conductivity test of Examples 47-57 and Comparative Example 6

[0104]

[0105] From the results in Table 6, it can be seen that the volume resistivity of the graphene oxide modified without using ionic liquid in Comparative Example 6 is significantly improved compared with Examples 47-57, indicating that the addition of ionic liquid can cooperate with graphene oxide to reduce the volume resistivity of the composite lithium-based grease, thereby improving the conductivity of the lubricant; from the results of Examples 47-50, it can be seen that the type of ionic liquid has a significant effect on the volume resistivity. The use of graphene oxide modified with ionic liquid greatly reduces the volume resistivity of the grease, indicating that conductive ionic liquids can greatly improve the conductivity of the grease; in addition, under the same cation, the volume resistivity of the graphene oxide modified with trifluoromethanesulfonyl is lower than that of the graphene oxide modified with hexafluorophosphate; when When the anions are the same, the volume resistivity of the grease increases with the increase of the length of the alkyl carbon chain of the cation. Since the anions are the same, the van der Waals force and the associative force are relatively reduced, and the conductivity increases with the increase of the cation chain length; for ionic liquids with the same cations, smaller anions have more dispersed charges, resulting in weaker hydrogen bonds and binding with cations, thereby increasing the conductivity of the grease; it can be seen from the results of Examples 51-54 that with the increase of the ionic liquid content, the volume resistivity of the composite lithium-based grease slowly decreases, but the decrease is small; the results of Examples 51 and 55-57 show that with the increase of the amount of modified graphene oxide, the volume resistivity shows a trend of first increasing and then decreasing. Compared with traditional ionic liquids, the bis(trifluorosulfonate) ester ionic liquid coordinates the polarity and conductivity of ionic liquids. On the premise of meeting the conductivity requirements, the oil solubility is improved, so that the ionic liquid can be stably dispersed in the grease for a long time. The addition of graphene oxide solid is difficult to enter the oil film at the lubrication interface, and the increase in dosage hinders its conductive effect, while the addition of ionic liquid can enter the oil film, which has a more obvious effect of reducing interface resistance and friction and anti-wear. However, the addition of excessive ionic liquid reduces the viscosity of the composite lithium-based grease and reduces the basic performance of the grease. From the results in Table 6, it can be seen that the volume resistivity of the composite lithium-based grease obtained by using bis(trifluorosulfonate) ester to modify graphene oxide and control the dosage is 0.82×10 9 Ω·cm, with significantly improved conductivity.

[0106] Embodiment 59

[0107] Preparation of α-layered zirconium phosphate:

[0108] Fully stir and dissolve 5 parts of sodium chloride, 10 parts of zirconium oxychloride octahydrate and 300 ml of distilled water in a reactor to obtain a solution; add 20 parts of phosphoric acid to the solution, stir evenly and age at room temperature for 24 hours to obtain a mixture; put the mixture into an oven, react at 160°C for 36 hours to obtain a reactant; wash the reactant with distilled water to neutrality, naturally air-dry and grind to obtain the α-layered zirconium phosphate; the particle size of the α-layered zirconium phosphate is 600nm.

[0109] The preparation method and parameter conditions of the composite lithium-based grease are prepared by referring to Example 35.

[0110] Embodiment 60

[0111] Fully stir and dissolve 8 parts of sodium chloride, 10 parts of zirconium oxychloride octahydrate and 300 ml of distilled water in a reactor to obtain a solution; add 20 parts of phosphoric acid to the solution, stir evenly and age at room temperature for 24 hours to obtain a mixture; put the mixture into an oven, react at 180°C for 36 hours to obtain a reactant; wash the reactant with distilled water to neutrality, naturally air-dry and grind to obtain the α-layered zirconium phosphate; the particle size of the α-layered zirconium phosphate is 700 nm.

[0112] The preparation method and parameter conditions of the composite lithium-based grease are prepared by referring to Example 35.

[0113] Embodiment 61

[0114] 10 parts of sodium chloride, 10 parts of zirconium oxychloride octahydrate and 300 ml of distilled water are fully stirred and dissolved in a reactor to obtain a solution; 20 parts of phosphoric acid are added to the solution, stirred evenly and aged at room temperature for 24 hours to obtain a mixture; the mixture is placed in an oven and reacted at 200° C. for 36 hours to obtain a reactant; the reactant is washed with distilled water to neutrality, naturally air-dried and ground to obtain the α-layered zirconium phosphate; the particle size of the α-layered zirconium phosphate is 800 nm; the SEM image of the α-layered zirconium phosphate is as shown Figure 1 shown.

[0115] The preparation method and parameter conditions of the composite lithium-based grease are prepared by referring to Example 35.

[0116] The preparation methods and parameter conditions of Examples 62-68 refer to those of Example 54, and the differences are shown in Table 7.

[0117] Table 7 Component dosage of Examples 59-68

[0118] Example α-Layered zirconium phosphate particle size / nm α-Layered zirconium phosphate dosage / part Calcium carbonate dosage / portion Embodiment 59 600 5 3 Embodiment 60 700 5 3 Embodiment 61 800 5 3 Embodiment 62 600 1 3 Embodiment 63 600 3 3 Embodiment 64 600 8 3 Embodiment 65 600 10 3 Embodiment 66 600 5 1 Embodiment 67 600 5 2 Embodiment 68 600 5 5

[0119] Comparative Example 7 refers to the preparation method and parameter conditions of Example 59, except that no α-layered zirconium phosphate and calcium carbonate are added.

[0120] Comparative Example 8 refers to the preparation method and parameter conditions of Example 59, except that no calcium carbonate is added.

[0121] Example 69 Friction resistance test

[0122] The composite lithium-based greases prepared in Examples 59-68 and Comparative Examples 7-8 were subjected to wear reduction and anti-wear tests using a German OPTIMOL SRV-V friction and wear tester; load 300N, frequency 50HZ, stroke 1mm, temperature 80°C, time 60min, and the results are shown in Table 8; the volume wear of the steel disc and the wear spot diameter of the steel ball change with the amount of α-layered zirconium phosphate as shown in Table 8. Figure 2 shown.

[0123] Table 8 Friction resistance test of Examples 59-68 and Comparative Examples 7-8

[0124]

[0125]

[0126] From the results in Table 8, it can be seen that in Comparative Example 7, α-layered zirconium phosphate and calcium carbonate were not added as extreme pressure anti-wear agents, and the friction coefficient of the composite lithium grease obtained was high, and the wear amount and wear spot diameter were significantly increased compared with Examples 59-68; Comparative Example 8 added α-layered zirconium phosphate, and no calcium carbonate was added to assist, and the pressure reduction and anti-wear performance of the grease obtained was significantly improved compared with Comparative Example 8, but there was still a gap compared with the examples, indicating that calcium carbonate can synergize with zirconium phosphate to change the extreme pressure and anti-wear performance of the grease; From the results of Examples 59-61, it can be seen that with the change of the particle size of α-layered zirconium phosphate, there is almost no effect on the friction performance of the grease, and the addition of composite calcium carbonate compensates for the friction deterioration caused by pitting; From the results of Examples 59 and Examples 62-65, it can be seen that with the increase of the amount of α-layered zirconium phosphate, the volume wear amount of the steel disc is increased. It shows a significant reduction, the wear spot diameter and the friction coefficient are significantly reduced, and the friction resistance is improved; zirconium phosphate has a layered structure, and during the friction process, it produces slippage between layers on the friction surface, which hinders the direct contact of the metal surface, effectively reduces the friction and wear of the metal, and increases the load-bearing capacity of the grease. At the same time, the presence of phosphorus can effectively improve the anti-wear ability of the grease and reduce the friction of the metal surface under medium load conditions; It can be seen from the results of Examples 59 and 66-68 that changing the amount of calcium carbonate has a certain effect on the friction coefficient and average wear spot diameter of the grease. By compounding two calcium carbonates with different particle sizes, the lubrication performance of the grease can be improved according to the needs under different working conditions. Once pitting occurs on the tooth surface, the two calcium carbonates can fill and remedy the pitting site in time to avoid expansion, thereby extending the service life of the machine. Comprehensive Table 8 and Figure 2The results show that the composite lithium-based grease prepared by compounding α-layered zirconium phosphate and calcium carbonate has a steel ball wear spot diameter of 0.35 mm and an average friction coefficient of 0.091, which has significantly improved pressure relief and anti-wear properties.

[0127] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a multi-purpose composite lithium-based grease, characterized in that: The composite lithium-based grease comprises 75-100 parts of base oil, a composite lithium-based thickener, and additives; The composite lithium-based thickener comprises 5-10 parts of 12-hydroxystearic acid, 1.5-4 parts of stearic acid, 2.5 parts of auxiliary acid, and 0.8-2 parts of lithium hydroxide; The additives include 5-15 parts of modified graphene oxide, 4-13 parts of anti-wear agent, 0.5 parts of antioxidant, and 0.5 parts of rust inhibitor; The modified graphene is prepared by modifying graphene oxide and ionic liquid in a ratio of 1-4:6-9; The preparation method of the multi-purpose composite lithium-based grease comprises the following steps: The lithium hydroxide is added into deionized water and stirred to obtain a lithium hydroxide solution; 50% of the base oil, the 12-hydroxystearic acid and the stearic acid are added into a flask to obtain a dissolving system; the lithium hydroxide solution is added into the dissolving system, the temperature is raised to 95-100° C., and the system is saponified for 2 hours to obtain a system 1; the auxiliary acid is added into the system 1, the remaining amount of the lithium hydroxide solution is raised to 120-130° C., and the system is saponified for 1 hour to obtain a system 2; the system 2 is raised to 180-190° C., and the system is stirred and kneaded for 3 hours. 0min to obtain system three; add 25% of the base oil in total to the system three, slowly heat up to 220-225°C, and refine for 20min to obtain system four; add the remaining base oil to the system four, cool to 120°C, and keep warm for 10min to obtain composite grease; add the modified graphene oxide, the anti-wear agent, the antioxidant, and the rust inhibitor to the composite grease, stir at 90°C for 30min to obtain a mixture; transfer the mixture to a degassing kettle for degassing, filter, and package to obtain the composite lithium-based grease.

2. The method for preparing a multi-purpose composite lithium-based grease according to claim 1, characterized in that: The base oil is selected from one of modified castor oil, white oil, naphthenic oil, polyalphaolefin oil, pentaerythritol ester and dioleyl phosphate.

3. The method for preparing a multi-purpose composite lithium-based grease according to claim 2, characterized in that: The preparation method of the modified castor oil comprises the following steps: Castor oil, glacial acetic acid and phosphoric acid are added into a three-necked flask to obtain a mixture; the mixture is stirred, the temperature is raised to 70° C., 30% H2O2 solution is slowly added dropwise into the mixture, and the mixture is kept warm for 4 hours to obtain a reaction solution; the reaction solution is extracted with petroleum ether, rotary evaporated, and vacuum dried to obtain epoxidized castor oil; the epoxidation degree of the epoxidized castor oil is 0.5-2.2 mol / kg; The modifier is added into a three-necked flask, and 50 ml of ethanol is added and stirred to dissolve to obtain a solution; 100 parts of the epoxidized castor oil is slowly added into the solution, and the reaction is carried out at 50° C. for 2 hours to obtain a reaction liquid; the reaction liquid is cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried at 80° C. for 2 hours to obtain the modified castor oil.

4. The method for preparing a multi-purpose composite lithium-based grease according to claim 3, characterized in that: The modifier is selected from one of polymethacrylate, polyethylene, epoxy resin E42, epoxy resin E44, and bisphenol F; the amount of the modifier is 1-5 parts.

5. The method for preparing a multi-purpose composite lithium-based grease according to claim 1, characterized in that: The auxiliary acid is selected from one of azelaic acid, adipic acid, stearic acid, dodecanoic acid, sebacic acid, boric acid, terephthalic acid, and dodecanedioic acid.

6. The method for preparing a multi-purpose composite lithium-based grease according to claim 1, characterized in that: The ionic liquid is selected from one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-decyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium di(trifluoromethylsulfonyl)imide, 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and bistrifluorosulfonate.

7. The method for preparing a multi-purpose composite lithium-based grease according to claim 1, characterized in that: The preparation method of modified graphene oxide comprises the following steps: Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:1 to obtain a mixed acid solution; graphite and a 30% hydrogen peroxide solution are added to the mixed acid solution, and an ultrasonic reaction is performed for 2 hours to obtain a graphene solution; the graphene solution is centrifuged to obtain a solid separation; the solid separation is washed with a hydrochloric acid solution with a volume fraction of 10%, washed with deionized water, and vacuum dried at 80°C to obtain graphene oxide; the graphene oxide is added to anhydrous acetone, the ionic liquid is added under stirring, and ultrasonic dispersion is performed to obtain a mixed solution; the mixed solution is ground at room temperature for 4 hours to obtain a grind; the grind is placed in a vacuum drying oven and dried at 80°C for 24 hours to obtain the modified graphene oxide.

8. The method for preparing a multi-purpose composite lithium-based grease according to claim 1, characterized in that: The anti-wear agent is selected from a mixture of α-layered zirconium phosphate and calcium carbonate; the α-layered zirconium phosphate is used in an amount of 1-10 parts, and the particle size is 600-800nm; the calcium carbonate is used in an amount of 1-5 parts.

9. The method for preparing a multi-purpose composite lithium-based grease according to claim 1, characterized in that: The antioxidant is selected from tert-butyl-4-hydroxyanisole, and the rust inhibitor is selected from zinc naphthenate.

10. A multi-purpose lithium-based composite grease, characterized in that: The composite lithium-based grease comprises the base oil, the composite lithium-based thickener, the modified graphene oxide, the anti-wear agent, the antioxidant, and the rust inhibitor; the composite lithium-based grease is prepared by the preparation method according to any one of claims 1 to 9; the working cone penetration of the composite lithium-based grease is 242 / 0.1mm, and the extended working cone penetration is 275 / 0.1mm; the dropping point of the composite lithium-based grease is 326°C, and the steel mesh oil separation rate is 1.28%; the copper sheet acid corrosion and steel sheet acid corrosion of the composite lithium-based grease are 1a and 1a respectively; the volume resistivity of the composite lithium-based grease is 0.82×10 9 Ω·cm; the diameter of the steel ball wear spot of the composite lithium-based grease is 0.35mm, and the average friction coefficient is 0.091.

Citation Information

Patent Citations

  • Complex lithium-base lubricating grease and production technique thereof

    CN102051257B

  • Silicon-based lubricating grease composition for electrical contact, and preparation method thereof

    CN102618359B

  • Environmentally friendly lubricating grease with high lubrication performance and its preparation method

    CN109536260B

  • Lithium-based grease and its preparation method

    CN109810748B

  • A lubricating grease, its preparation method and application

    CN112877121B